Antibiofilm Activity of Mangosteen (Garcinia mangostana L.) Flavonoids against Streptococcus mutans Bacteria - Sri Kunarti; Aulia Ramadhani; Laskmiari Setyowati (Universitas Airlangga, 2020)
Background: Dental caries is one of the most common infectious diseases and often occurs in the community caused by bacteria. Attached bacteria in the tooth surface for a long time will form a biofilm and will lead to demineralization characterized by damage in the structure of the tooth enamel. The bacteria that cause dental caries and can form biofilms is Streptococcus mutans. The bacteria inside biofilms are more resistant to antibacterial agents. Flavonoids in mangosteen pericarp extract can be a cleaner alternative for the anti-biofilm cavity that has properties against Streptococcus mutans. Purpose: To determine the activity of flavonoids in mangosteen pericarp extract at a certain concentration against Streptococcus mutans bacteria. Methods: This study was a laboratory experimental study with a post-test only control group design. Streptococcus mutans were diluted according to the Mc Farland dilution standard 106 in Tryptic Soy Broth (TSB) medium and put in a flexible U-bottom microtiter plate. Then it was incubated for 5x24 hours and checked using crystal violet simple staining to see the formation of biofilms. Flavonoid extract of mangosteen pericarp performed serial dilution in a concentration of 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, 1.56%, and 0.78% was added, and the incubation process were conducted for 1x24 hours. OD (Optical Density) readings were done with a wavelength of 595 nm. Results: There was a significant difference between the test groups and the positive control group. The concentration of 100% had the anti-biofilm activity and showed the value of the highest percentage of inhibition, whilst the concentration of 0.78% showed a minimum biofilm inhibition concentration. The results were demonstrated by a statistical analysis test. Conclusion: Flavonoid extract of mangosteen pericarp at a certain concentration has anti-biofilm activity against Streptococcus mutans biofilm.